Promoted conversion of polysulfides by MoO2 inlaid ordered mesoporous carbons towards high performance lithium-sulfur batteries - Chen, Yawei; Niu, Shuzhang; Lv, Wei; Zhang, Chen; Yang, Quanhong (Chinese chemical letters, 2019)
A MoO2-ordered mesoporous carbon (M-OMC) hybrid was designed as the sulfur host, in which MoO2 is inlaid on the surface of ordered mesoporous carbons that can store active materials and provide fast electron transfer channel due to its ordered pore structure. The MoO2 can effectively prevent the migration of polysulfides through the chemical adsorption and promote the conversion of polysulfides towards Li-sulfur battery. [Display omitted] As polar materials, transition-metal oxides have shown great potentials to improve the adsorption of lithium polysulfides in lithium-sulfur batteries. Herein, a MoO2-ordered mesoporous carbon (M-OMC) hybrid was designed as the sulfur host, in which MoO2 is inlaid on the surface of ordered mesoporous carbons that can store active materials and provide fast electron transfer channel due to its ordered pore structure. The MoO2 can effectively prevent the migration of polysulfides through the chemical adsorption and promote the conversion of polysulfides towards Li-sulfur battery.